Scientific Production on GPS Trajectory Clustering: A Bibliometric Analysis - Reyes, Gary; Tolozano-Benites, Roberto; Lanzarini, Laura; Estrebou, César; Bariviera, Aurelio F. (ISPRS international journal of geo-information, 2025)
Clustering algorithms or methods for GPS trajectories are in constant evolution due to the interest aroused in part of the scientific community. With the development of clustering algorithms considered traditional, improvements to these algorithms and even unique methods considered as “novel” for science have emerged. This work aimed to analyze the scientific production that exists around the topic “GPS trajectories clustering” by means of bibliometrics. Therefore, a total of 559 articles from the main collection of Scopus were analyzed, initially filtering the generated sample to discard any articles that did not have a direct relationship with the topic to be analyzed. This analysis establishes an ideal environment for other disciplines and researchers since it provides a current state of the trend of the subject of study in their field of research.